Implications of constitutional recognition for Australian local government - Australia. Advisory Council for Inter-government Relations (Hobart : Tasmanian Government Printer, 1985)
"Relationships reference'
"Relationships reference".
Includes bibliographical references.
Chairman: R.C. Gates
Keywords: Local government -- Australia; Australia -- Politics and government